From bench to bedside: an interdisciplinary journey through the gut-lung axis with insights into lung cancer and immunotherapy - Dora, David; Szőcs, Emőke; Soós, Ádám; Halasy, Viktória; Somodi, Csenge; Mihucz, Anna; Rostás, Melinda; Mógor, Fruzsina; Lohinai, Zoltan; Nagy, Nándor (Frontiers in Immunology, 2024)
This comprehensive review undertakes a multidisciplinary exploration of the gut-lung axis, from the foundational aspects of anatomy, embryology, and histology, through the functional dynamics of pathophysiology, to implications for clinical science. The gut-lung axis, a bidirectional communication pathway, is central to understanding the interconnectedness of the gastrointestinal-and respiratory systems, both of which share embryological origins and engage in a continuous immunological crosstalk to maintain homeostasis and defend against external noxa. An essential component of this axis is the mucosa-associated lymphoid tissue system (MALT), which orchestrates immune responses across these distant sites. The review delves into the role of the gut microbiome in modulating these interactions, highlighting how microbial dysbiosis and increased gut permeability ("leaky gut") can precipitate systemic inflammation and exacerbate respiratory conditions. Moreover, we thoroughly present the implication of the axis in oncological practice, particularly in lung cancer development and response to cancer immunotherapies. Our work seeks not only to synthesize current knowledge across the spectrum of science related to the gut-lung axis but also to inspire future interdisciplinary research that bridges gaps between basic science and clinical application. Our ultimate goal was to underscore the importance of a holistic understanding of the gut-lung axis, advocating for an integrated approach to unravel the complexities of human health and disease.